2022
DOI: 10.1136/jitc-2021-004159
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell-mediated cross presentation of tumor-derived peptides is biased against plasma membrane proteins

Abstract: BackgroundFor effective tumor elimination, cytotoxic CD8+ T cells must recognize tumor-derived antigens presented on class I major histocompatibility complex (MHC-I). Despite a general association between the expression of immunogenic antigens, typically neoantigens, and response to immunotherapy, the majority of patients lack strong endogenous responses to most putative neoantigens due to mechanisms that are not well understood. Cytotoxic CD8+ T-cell responses are induced by dendritic cells (DCs) cross-presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Of note, the pattern of responding neoAgs was modified by cDC1 depletion or, conversely, by cDCs expansion, suggesting that weaker neoAgs (low pMHC-I affinity or low expression) may preferentially require boosting of cross-presenting cDC1. In line with this concept, recent findings showed that DCs can shape the final repertoire of anti-tumoral T cells 53 .…”
Section: Discussionmentioning
confidence: 76%
“…Of note, the pattern of responding neoAgs was modified by cDC1 depletion or, conversely, by cDCs expansion, suggesting that weaker neoAgs (low pMHC-I affinity or low expression) may preferentially require boosting of cross-presenting cDC1. In line with this concept, recent findings showed that DCs can shape the final repertoire of anti-tumoral T cells 53 .…”
Section: Discussionmentioning
confidence: 76%
“…Of note, the pattern of responding neoAgs was modified by cDC1 depletion or, conversely, by cDCs expansion, suggesting that weaker neoAgs (low pMHC-I affinity or low expression) may preferentially require boosting of crosspresenting cDC1. In line with this concept, recent findings showed that cDCs can shape the final repertoire of anti-tumoral T cells (Fessenden et al, 2022).…”
Section: Discussionmentioning
confidence: 76%
“…Recently, reports have also highlighted that the subcellular localization of a protein plays a key role in the way it is mounted on MHC and on modulating the immune response. 51 , 52 , 53 Particularly, Castro et al. 52 have demonstrated that neoepitopes derived from proteins from accessible locations were associated with a better neoantigen vaccination response and enhanced success of ICI.…”
Section: Discussionmentioning
confidence: 99%